Molecular Chains: Arranging and Programming Logic Gates - Leisegang, Markus; Christ, Andreas; Haldar, Soumyajyoti; Heinze, Stefan; Bode, Matthias (Nano letters, 2021)
One particularly fascinating vision for charge-operated devices is the controlled assembly of structures from single surface-deposited molecules. Here, we report on the assembly of linear clusters that consist of phthalocyanine (H Pc) molecules on a Ag(111) surface. The molecules are imaged as well as manipulated with a low-temperature scanning tunneling microscope (STM). Upon deprotonation of every second H Pc, the resulting HPc molecule exhibits an isomeric bistability which can be used as inputs in logic gates. Combining our STM measurements with density functional theory calculations we show that the HPc isomers exhibit a repulsive electrostatic interaction with adjacent H Pc molecules which, due to the asymmetric charge distribution on HPc, results in a counterclockwise or clockwise molecule tilt of the latter, thereby defining the logic 0 and 1 of the output. It is shown that information can be relayed along molecule chains over distances equivalent to at least nine molecules.